К вопросу о формировании политической элиты в Сирии в мандатный период - Манукян, Сурен (Ասողիկ հրատ.)
Syria appeared under the French mandate after the collapse of the Ottoman Empire and short-time independence in 1918-20. Simultaneousiy Syrien identity and Syrian political- elite as its main component conti nued its formation in 3 tendencies: rise of army, embracingthe nationalism as an ideal program of State development and arise of Islam as an alternative trend. The influence of ethno-religious minorities played аsignificant role in these processes.
Keywords: История; Политика